The next gen leader : cutting edge strategies to make you the leader you were born to be - McMillan, Robert C. (Career Press, 2014)
While today's global economy is experiencing a significant cycle of out-sourcing across industries, leadership cannot be outsourced; it must be organically transformed. The Next Gen Leader will show you how to discard outworn traditions and become the next-generation leader you were born to be! It is a system designed to help you maximize individual, team, and organizational leadership potential, regardless of your position, pay, or power.